2021
DOI: 10.1186/s12978-021-01229-1
|View full text |Cite
|
Sign up to set email alerts
|

The timing for initiating estrogen stimulation in artificial cycle for frozen-thawed embryo transfer can be flexible

Abstract: Background There remains a lack of evidence to demonstrate whether the initiation time of estrogen stimulation is flexible in the proliferative endometrial phase during the artificial cycle for frozen-thawed embryo transfer (AC-FET). Methods FET records were retrospectively reviewed from a large university-affiliated reproductive medicine center. Only the patients who were undergoing their first embryo transfer with a single blastocyst in the AC-FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…At present, few studies have addressed the effect of the number of days of continuous oestrogen administration on receiving autologous oocyte-derived frozen embryo transfer. Ying et al [ 24 ] found that biochemical and clinical pregnancy rates were significantly higher in the later oestrogen initiation group compared with the early oestrogen initiation group, however, ongoing pregnancy rates were not significantly different between groups. However, this study did not observe the effect of duration of oestrogen on live birth rate.…”
Section: Discussionmentioning
confidence: 99%
“…At present, few studies have addressed the effect of the number of days of continuous oestrogen administration on receiving autologous oocyte-derived frozen embryo transfer. Ying et al [ 24 ] found that biochemical and clinical pregnancy rates were significantly higher in the later oestrogen initiation group compared with the early oestrogen initiation group, however, ongoing pregnancy rates were not significantly different between groups. However, this study did not observe the effect of duration of oestrogen on live birth rate.…”
Section: Discussionmentioning
confidence: 99%
“…At present, few studies have addressed the effect of the number of days of continuous oestrogen administration on receiving autologous oocyte-derived frozen embryo transfer. Ying et al 24 found that biochemical and clinical pregnancy rates were signi cantly higher in the later oestrogen initiation group compared with the early oestrogen initiation group, however, ongoing pregnancy rates were not signi cantly different between groups. However, this study did not observe the effect of duration of oestrogen on live birth rate.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, the onset of oestrogen therapy (day 2-5 of cycle vs. day 6 onwards), and not its length, has been proven to have a significant impact on endometrial thickness, as well as on biochemical and clinical pregnancy, being higher in the late onset group. In contrast, the same relationship has not been proven for ongoing pregnancy rate ( 9 ).…”
Section: Introductionmentioning
confidence: 97%